2013
DOI: 10.1172/jci60083
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 regulates arginase-I in myeloid-derived suppressor cells from cancer patients

Abstract: Myeloid-derived suppressor cells (MDSC) play a key immunosuppressive role in various types

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
425
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 457 publications
(452 citation statements)
references
References 53 publications
16
425
1
Order By: Relevance
“…CD14 1 HLA-DR 2/low cells express STAT3 and pSTAT3 associated with increased CCL2 A previous study showed that STAT3 signaling plays an important role in CD14 1 HLA-DR 2/low MDSCs expansion 24 . We examined whether STAT3 signaling was also involved in the expansion of CD14 1 HLA-DR 2/low MDSCs through crosstalk between CD14 1 myelomonocytic cells and trophoblast cells and whether CCL2 mediates this process.…”
Section: Resultsmentioning
confidence: 93%
“…CD14 1 HLA-DR 2/low cells express STAT3 and pSTAT3 associated with increased CCL2 A previous study showed that STAT3 signaling plays an important role in CD14 1 HLA-DR 2/low MDSCs expansion 24 . We examined whether STAT3 signaling was also involved in the expansion of CD14 1 HLA-DR 2/low MDSCs through crosstalk between CD14 1 myelomonocytic cells and trophoblast cells and whether CCL2 mediates this process.…”
Section: Resultsmentioning
confidence: 93%
“…Interestingly, there appears to be a consensus regarding activation of Janus kinase protein and STAT 3 and 5 (47). Indeed, some reports argue that STAT 3 and 5 regulate MDSC function in both mice and humans (9,10,48 (20). Thus, these findings appear to be important in terms of MDSC induction by mTOR inhibitors or other immunosuppressive drugs in the context of clinical organ transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it would be interesting to examine the mechanisms by which MDSCs suppress immunological rejection and to identify the specific molecules involved; such knowledge could then be applied to clinical organ transplantation. Intensive research on MDSCs has shed light on the factors that influence their kinetics and function (8)(9)(10)(11). However, the exact mechanisms by which MDSCs suppress immune responses are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ability of MDSCs to suppress T-cell proliferation may be central to tumor formation (43)(44)(45). ARG-1-mediated depletion of L-arginine, ROS production, and STAT3 activation regulate the functions of MDSCs and have been reported to be the mechanisms responsible for the ability of MDSC to suppress T-cell functions (29)(30)(31). Through FACS analysis using murine spleen tissues, we demonstrated that calcitriol attenuated the increases in the levels of ROS, activated STAT3 and suppressive ability of T-cell proliferation in MDSCs obtained from IL6-stimulated or 4-NQOtreated mice.…”
Section: Discussionmentioning
confidence: 99%
“…6A, calcitriol abrogated the recruitment of MDSCs induced by IL6 stimulation in C57 mice. MDSCs are a heterogeneous cell population characterized by the ability to suppress T-cell functions including proliferation via a range of mechanisms, including reactive oxygen species (ROS) production and increases in the activated STAT3 levels (28)(29)(30)(31). Therefore, to further assess whether calcitriol treatment impaired the function of the recruited MDSCs, we examined the levels of p-STAT3 and ROS and the suppressive ability of Tcell proliferation in MDSCs from IL6-stimulated or 4-NQOtreated mice with or without calcitriol treatment.…”
Section: Effects Of Calcitriol On the Recruitment And Function Of Mdsmentioning
confidence: 99%